Cement-based mortar patch repair of RC columns. Comparison with all-four-sides and one-side repair. (20th October 2018) - Ortega, Irene; Pellicer, Teresa M.; Calderón, Pedro A.; Adam, Jose M.
Graphical abstract: Highlights: Patch repairs are widely used for local damage in RC columns. 15 patch-repaired RC columns were tested at the ICITECH. The paper analyses the effectiveness of patch repairs on RC columns. Patch repair is compared with: all-four-sides and one-side repair. Abstract: This paper describes an experimental study on patch-repaired reinforced concrete columns subjected to axial loads until failure. The behaviour of four series of columns repaired with Class R3 and R4 cement-based mortar was analysed both with and without a bonding agent. The results obtained were compared with control series of undamaged and damaged but unrepaired columns to determine the effectiveness of the repairs and the subsequent improvement in the behaviour of the columns. The results of this study were compared with those of previous work by the authors on the analysis of all-four-side repairs and one-side repairs. The conclusion reached was that patch repairs are highly effective as compared to the other techniques studied and that using Class R3 mortar achieves better results on damaged columns made with low-quality concrete. It was also concluded that applying a bonding agent does not improve the results, although this element was found to be necessary to prevent the premature detachment of the repair when there is a substantial difference between the stiffness of the column concrete and that of the mortar used in the repairs.